In Silico structural analysis of the complex PSKR receptor like Kinase, Pamp Phytosulfokine and SERk1 co-receptor - Thakur, Hasnain Nizam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.